If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8t + -5 + t + -1 = 0 Reorder the terms: -5 + -1 + -8t + t = 0 Combine like terms: -5 + -1 = -6 -6 + -8t + t = 0 Combine like terms: -8t + t = -7t -6 + -7t = 0 Solving -6 + -7t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -7t = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -7t = 0 + 6 -7t = 0 + 6 Combine like terms: 0 + 6 = 6 -7t = 6 Divide each side by '-7'. t = -0.8571428571 Simplifying t = -0.8571428571
| 4.2x-2.58=2.52-4.3x | | 6(3x-4)= | | 0=5-2(3+4x) | | 219-3x=33x+19 | | 2-3(x+4)=4 | | 5-2x-9=7x+18 | | x^3-4x^2-15x+18=0 | | 6c^2+13c-28=0 | | 2x+104=7x-11 | | 8k^2-98=0 | | -9+y=1 | | (-2+4)*6+(-3)= | | 11x+19=2x+289 | | 35(8-x)=595 | | 9+y=1 | | y=x+-3 | | 0=2w^2+4w-3w^2 | | 12(15+x)=348 | | 22x^2=36 | | 4t^2-24t-24=0 | | 5-9(x+5)-7=5+3(9-3x)-81 | | 2b+18-4d=60 | | 3w^2=2w^2+4w | | 26x+y=34 | | -3t^2+108=0 | | 9x+19=28-2x | | 10-9x=26-23x | | (5a+4)-(5a+3)= | | 135-7x=8x+15 | | 6p^2-864=0 | | 8x-(3x+7)=13 | | 3d+13=-8 |